1983
DOI: 10.1139/m83-114
|View full text |Cite
|
Sign up to set email alerts
|

Competitive adherence as a mechanism of bacterial interference

Abstract: To determine whether competition among bacteria for specific attachment sites on host cells can explain bacterial interference, Staphylococcus aureus strain 502A was tested in turn against two different nasal coryneforms, a strain of Pseudomonas aeruginosa, and a virulent strain of S. aureus, all in the presence of nasal mucosal cells. Particularly examined was the influence of sequence in which bacteria were presented to the nasal cells in comparison with initial mixtures and individual suspensions. Results p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
28
0
2

Year Published

1987
1987
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(30 citation statements)
references
References 0 publications
0
28
0
2
Order By: Relevance
“…Many mechanisms by which bacteria and their interactions prevent the invasion and colonisation of pathogenic microorganisms have been proposed, but are not all fully understood. Occupation of the host's epithelial surfaces by bacterial flora and thus, prevention of pathogen adherence on these cells [5,6], can be particularly important, given that adherence on mammary epithelial cells by M. haemolytica is necessary for leucotoxin production [55]. Since staphylococci adhere to mammary epithelial cells forming biofilms [13,42], one may postulate this as the primary mechanism by which the protective effects took place in the present experiments.…”
Section: Discussionmentioning
confidence: 84%
“…Many mechanisms by which bacteria and their interactions prevent the invasion and colonisation of pathogenic microorganisms have been proposed, but are not all fully understood. Occupation of the host's epithelial surfaces by bacterial flora and thus, prevention of pathogen adherence on these cells [5,6], can be particularly important, given that adherence on mammary epithelial cells by M. haemolytica is necessary for leucotoxin production [55]. Since staphylococci adhere to mammary epithelial cells forming biofilms [13,42], one may postulate this as the primary mechanism by which the protective effects took place in the present experiments.…”
Section: Discussionmentioning
confidence: 84%
“…Over the years, many studies have observed interactions between various bacterial species and viruses carried in the upper respiratory tract. [26][27][28][29][30] These bacteria and viruses compete for space and resources 25,30,31 and in some cases, such as influenza virus and S. pneumoniae, the virus and bacteria act synergistically to cause increased S. pneumoniae adhesion to host cells. 32 The most clinically relevant and commonly studied interactions and competition are those between the upper respiratory tract pathogens, namely S. pneumoniae, S. aureus, H influenzae, and M. catarrhalis.…”
mentioning
confidence: 99%
“…47 The role of the immune system in the bacterial interference While some studies focused on potential direct mechanisms of interference, i.e. competition for space and resources 30,31,46 or direct inhibition through bactericidal factors, 18,21,41,48 the fact that S. aureus and S. pneumoniae colonize closely related, yet not precisely the same region in the upper respiratory niche, suggests that indirect inhibition, such as immune mediated inhibition is more plausible. The concept of interspecies immune-mediated cross-reactivity is not new, with some examples being cowpox and small pox, as discovered by Edward Jenner, 49 or certain enteric commensal Escherichia coli.…”
mentioning
confidence: 99%
“…Ninguno de estos pacientes desarrolló posteriormente infección por este patógeno. Por otro lado, la presencia importante de S. epidermidis en casi todos los pacientes, el cual se une a los receptores de los queratinocitos, y bloquea la adhesión de S. aureus, a través de un proceso conocido como interferencia bacteriana, podría explicar el reducido número de casos en que se aisló S. aureus 15,16 . Dentro de los bacilos que colonizan la piel, uno de los géneros más prevalentes es Propionibacterium, anaerobio estricto, que no fue contemplado en este estudio.…”
Section: Artículo Originalunclassified